2021
DOI: 10.2196/26378
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Twitter by Medical Journals: Systematic Review of the Literature

Abstract: Background Medical journals use Twitter to engage and disseminate their research articles and implement a range of strategies to maximize reach and impact. Objective This study aims to systematically review the literature to synthesize and describe the different Twitter strategies used by medical journals and their effectiveness on journal impact and readership metrics. Methods A systematic search of the lit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…His work has informed safe coaching techniques and South African Rugby’s BokSmart injury intervention programme4 5 and, along with leading experts, produced a consensus document for video analysis in rugby 6. Sharief’s further research interest in science communication7 and stakeholder engagement8 is reflected in two leading science communication websites—HealthScienceReviews.com (https://healthsciencereviews.com) and RugbyScientists.com (https://rugbyscientists.com).…”
Section: The Pathmentioning
confidence: 99%
“…His work has informed safe coaching techniques and South African Rugby’s BokSmart injury intervention programme4 5 and, along with leading experts, produced a consensus document for video analysis in rugby 6. Sharief’s further research interest in science communication7 and stakeholder engagement8 is reflected in two leading science communication websites—HealthScienceReviews.com (https://healthsciencereviews.com) and RugbyScientists.com (https://rugbyscientists.com).…”
Section: The Pathmentioning
confidence: 99%
“… 6 For peer-reviewed journals, social media represents an opportunity to engage with readership, share published articles, and facilitate discussion on the latest medical research, with previous studies suggesting that an active social media presence may contribute to increased research impact. 7 …”
Section: Introductionmentioning
confidence: 99%
“…6 For peer-reviewed journals, social media represents an opportunity to engage with readership, share published articles, and facilitate discussion on the latest medical research, with previous studies suggesting that an active social media presence may contribute to increased research impact. 7 While several studies have recently reported on social media usage in medical specialties including dermatology, orthopaedics, urology, and neurosurgery, information on the current state of social media utilization by ophthalmology peer-reviewed journals, professional societies, and/or eye health organizations remains limited. 6,[8][9][10] As recently as 2014, social media was infrequently utilized in medicine, limited in scope (platforms such as Instagram not yet widespread), and unpopular amongst older Americans.…”
Section: Introductionmentioning
confidence: 99%
“…They also found how interjournal communications can be detected within the same citation index but hardly across separate indices (Raamkumar et al, 2018). They identified the factors that determined 'successful' Tweets (Wadhwa et al, 2017) such as interactive user mentions (Robbins et al, 2019), infographics and online journal clubs (Erskine & Hendricks, 2021;Lasch & Heaton, 2022;Sarwal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%